Sistem Informasi Sebagai Peluang dan Tantangan Dakwah - Larasati, Dwi; Efendi, Erwan; Hasibuan, Sapriyani; Harahap, Rizky Padli; Gumala, Randy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Application of a management information system to the Da'wah Organization Management Organization, which entails knowledge of the management information system, its goals, benefits, and features, as well as the Da'wah Organization Organization's management information system, from which we can learn how to apply this In missionary organizations, there is management, which starts with data processing and ends with data programming. Information systems need to be capable of offering useful information to managers, especially for users, in order to support operations and management within an organization in an integrated manner. Today's organizations need the involvement of many more internal parties than they did in the past when it came to their role and involvement in the development and management of information systems. Keywords : Information System, Opportunities, Dawah